Pharmaceutical dosage forms : Parenteral medications. Vol. 3, regulations, validation and the future - Nema, Sandeep; Ludwig, John D. (New York : Informa Healthcare, 2010)
"A historical perspective of injectable drug therapy, common routes of administration, and biopharmaceutics of NCEs and NBEs. - An in-depth discussion on the preformulation and formulation of small and large molecules, including ophthalmic dosage forms. - A presentation of parenteral primary packaging options - glass and plastic containers, as well as elastomeric closures. - A definitive chapter on container-closure integrity. - New chapters on solubility and solubilization, formulation of depot delivery systems and biophysical/biochemical characterization of proteins"--Provided by publisher.
v. 1. Formulation and packaging -- v. 2. Facility design, sterilization, and processing -- v. 3. Regulations, validation, and the future.
Rev. ed. of: Pharmaceutical dosage forms, parenteral medications. 2nd ed., rev. and expanded. c1992-1993.
Includes bibliographical references and index.
Keywords: Parenteral solutions; Pharmaceutical technology; Infusions, Parenteral -- standards; Dosage Forms -- standards; Drug Delivery Systems -- methods; Pharmaceutical Preparations -- administration & dosage; Quality Control